ANALISIS SISTEM PROTEKSI KEBAKARAN AKTIF PADA RUMAH SAKIT GIGI DAN MULUT X DI KOTA BANDUNG - Muhammad Aulia UshSholeh; Suroto Suroto; Ida Wahyuni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
Dental and Oral Hospital (RSGM) is a building that has a high risk of fire. If RSGM experiences a fire, it will have a very severe impact. Therefore we need an active fire protection system to prevent and cope with fire hazards. The purpose of this study was to analyze the active fire protection system that is in X Dental and Oral Hospital in Bandung City referring to the Minister of Public Works Regulation No. 26/2008 and the Hospital Infrastructure Technical Guidelines, Active Fire Protection Systems. This type of research is a descriptive study using qualitative methods. Data collection was carried out by means of in-depth interviews online via telephone or chat, involving three main informants and three triangulation informants The results shows that the active fire protection system at X Oral and Dental Hospital was good enough at several points, such as: there was a written policy; has conducted hazard potential identification and risk assessment; The requirements and laws referred to by the hospital are not only K3 in general, but there are already special regulations regarding fire protection systems and have collaborated with the Fire Service and third parties related to APAR; The hospital already has a fire disaster management team. But it is also balanced with existing deficiencies such as policies that have not been conveyed to all workers and there are still active fire protection system equipment that are not yet available. Researchers suggest shows things to be improved in disseminating of the policies to all staffs and in providing all equipments of the active fire protection system.